The Association Between Duration and Posture in Laptop Use With Musculoskeletal Complaint in Bachelor Of Medicine Students, Faculty Of Medicine Udayana University - Devi, Natasha Pradnya; Dinata, I Made Krisna; Primayanti, I Dewa Ayu Inten Dwi; Adiputra, Luh Made Indah Sri Handari; Tirtayasa, Ketut (E-Jurnal Medika Udayana; Vol 13 No 11 (2024): E-Jurnal Medika Udayana, 2024)
The use of laptops is inseparable from people's lives. One of negative impacts from laptop usage is the musculoskeletal complaint. It is not yet known whether there is an association between duration and posture in laptop use in Bachelor of Medicine students, Faculty of Medicine, Udayana University. Therefore, this study aims to determine the association between duration and posture in laptop use with musculoskeletal complaint in Bachelor of Medicine Students. This study employed an analytic approach with cross sectional method. The research subjects were Bachelor of Medicine students in Udayana University, consisting of 84 people. Data regarding duration was obtained through a questionnaire. Data regarding posture was measured using RULA. Data related to musculoskeletal pain was measured using NBM questionnaire. Control variables were history of trauma or disease related to musculoskeletal complaints and room temperature. Bivariate analysis was performed using Spearman's Rho test. The results of this study showed 74 samples experienced low pain, while 10 other samples experienced moderate pain. The highest amount of pain was in the upper neck area. This study showed an association between the duration of laptop use with musculoskeletal complaint (p = 0.04; r = 0.22). There is also an association between body posture when using a laptop with musculoskeletal complaint (p = 0.009; r = 0.28). There is a weak relationship between duration and posture in the use of laptops with musculoskeletal complaint in students of the Bachelor of Medicine students, Faculty of Medicine, Udayana University. Keywords : laptop, duration, posture, musculoskeletal complaint